Proceedings of the 2nd International Conference on Electronics, Biomedical Engineering, and Health Informatics c - Triwiyanto, Triwiyanto; Rizal, Achmad; Caesarendra, Wahyu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents high-quality peer-reviewed papers from the International Conference on Electronics, Biomedical Engineering, and Health Informatics (ICEBEHI) 2021 held at Surabaya, Indonesia, virtually. The contents are broadly divided into three parts: (i) electronics, (ii) biomedical engineering, and (iii) health informatics. The major focus is on emerging technologies and their applications in the domain of biomedical engineering. It includes papers based on original theoretical, practical, and experimental simulations, development, applications, measurements, and testing. Featuring the latest advances in the field of biomedical engineering applications, this book serves as a definitive reference resource for researchers, professors, and practitioners interested in exploring advanced techniques in the field of electronics, biomedical engineering, and health informatics. The applications and solutions discussed here provide excellent reference material for future product development.
Analysis of Educational Data Mining Using WEKA for the Performance Students Achievements -- IoT-based Distributed Body Temperature Detection and Monitoring System for the Implementation of onsite Learning at Schools -- Improving The Quality And Education Systems Through Integration's Approach Of Data Mining Clustering In E-Learning -- Survey of Deep Learning on Identification of COVID-19 through X-Ray Images -- Half Bridge Operational Testing and Optimization for Chemiresistive Escherichia coli Bacteria Sensor Application -- Vital Sign Monitor Based On Telemedicine via Android.
Keywords: Electronics; Biomedical engineering; Medical informatics; Electronics and Microelectronics, Instrumentation; Biomedical Engineering and Bioengineering; Health Informatics; Biomedical engineering -- Technological innovations -- Congresses; Electronics -- Congresses; Medical informatics -- Congresses